Does Ownership Structure Affect the Relationship between Profitability and Dividend Policy? - Rudiningtyas, Dyah Arini; Handayati, Puji; Siswanto, Ely (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2025)
Purpose – This study examines the effect of ownership structure on the relationship between profitability and dividend policy in manufacturing companies listed on the Indonesia Stock Exchange from 2012 to 2023. Methodology/approach – This study employs a quantitative approach using secondary data from annual financial reports. A sample of 141 companies was selected using purposive sampling, resulting in 1,117 observations. The analysis was conducted using Moderated Regression Analysis (MRA) to test the moderating role of ownership structure in the profitability-dividend policy relationship. Findings – The results indicate that profitability and liquidity positively affect dividend policy, while leverage has a negative effect. Managerial ownership significantly reduces dividend payments, as managers prefer retained earnings for future growth. Institutional ownership, however, strengthens the relationship between profitability and dividend policy, acting as a monitoring mechanism to ensure optimal dividend distribution. Novelty/value – This study provides new insights into the moderating role of ownership structure in dividend policy decisions within the Indonesian manufacturing sector. The findings highlight the importance of institutional oversight in ensuring dividend payments align with shareholder interests, while managerial ownership tends to prioritize internal funding over distributions.